2017
DOI: 10.1103/physrevb.95.115137
|View full text |Cite
|
Sign up to set email alerts
|

Many-body correlations and coupling in benzene-dithiol junctions

Abstract: Most theoretical studies of nanoscale transport in molecular junctions rely on the combination of the Landauer formalism with Kohn-Sham density functional theory (DFT) using standard local and semilocal functionals to approximate exchange and correlation effects. In many cases, the resulting conductance is overestimated with respect to experiments. Recent works have demonstrated that this discrepancy may be reduced when including many-body corrections on top of DFT. Here we study benzene-dithiol (BDT) gold jun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 74 publications
(108 reference statements)
0
7
0
Order By: Relevance
“…GW self-energy has been recognized as a good approach to correct for this error and to describe more accurately the energy level alignment at the molecule-metal interface. However, it has been shown that GW corrections affect rather unoccupied orbitals (poorly described within the ground state DFT) while occupied levels (in particular, the HOMO) are only slightly altered 48,49 . Since the charge transport in M1 and M6 is dominated by the HOMO level, we hope that our mean-field DFT studies are good enough to provide reliable comparative results.…”
Section: Resultsmentioning
confidence: 99%
“…GW self-energy has been recognized as a good approach to correct for this error and to describe more accurately the energy level alignment at the molecule-metal interface. However, it has been shown that GW corrections affect rather unoccupied orbitals (poorly described within the ground state DFT) while occupied levels (in particular, the HOMO) are only slightly altered 48,49 . Since the charge transport in M1 and M6 is dominated by the HOMO level, we hope that our mean-field DFT studies are good enough to provide reliable comparative results.…”
Section: Resultsmentioning
confidence: 99%
“…In DFT+Σ, we introduce a separate self-energy Σ in the subspace of the central region Hamiltonian H to correct the KS eigenvalues for missing exchange and correlation effects (the Σ in DFT+Σ). While prior work has performed a more rigorous GW calculation on molecular junctions to evaluate Σ, ,, such an approach is not yet feasible for many increasingly complex systems of interest. Instead, here we work within the DFT+Σ framework described above, generalizing it to covalently bound junctions.…”
Section: Methodsmentioning
confidence: 99%
“…The approach used in this work is still based on the Landauer formalism, but with a corrected electronic structure. Along these lines several authors have already attempted to go beyond DFT+Landauer to describe quantum transport in molecular junctions, for example by using semi-empirical models like the image-charge DFT+Σ model 17 , or fully ab initio approaches 22,23 like GW or COHSEX. Such attempts remain rare in the literature.…”
Section: Introductionmentioning
confidence: 99%